-14+6(w+15)=13w+12+w

Simple and best practice solution for -14+6(w+15)=13w+12+w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14+6(w+15)=13w+12+w equation:


Simplifying
-14 + 6(w + 15) = 13w + 12 + w

Reorder the terms:
-14 + 6(15 + w) = 13w + 12 + w
-14 + (15 * 6 + w * 6) = 13w + 12 + w
-14 + (90 + 6w) = 13w + 12 + w

Combine like terms: -14 + 90 = 76
76 + 6w = 13w + 12 + w

Reorder the terms:
76 + 6w = 12 + 13w + w

Combine like terms: 13w + w = 14w
76 + 6w = 12 + 14w

Solving
76 + 6w = 12 + 14w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-14w' to each side of the equation.
76 + 6w + -14w = 12 + 14w + -14w

Combine like terms: 6w + -14w = -8w
76 + -8w = 12 + 14w + -14w

Combine like terms: 14w + -14w = 0
76 + -8w = 12 + 0
76 + -8w = 12

Add '-76' to each side of the equation.
76 + -76 + -8w = 12 + -76

Combine like terms: 76 + -76 = 0
0 + -8w = 12 + -76
-8w = 12 + -76

Combine like terms: 12 + -76 = -64
-8w = -64

Divide each side by '-8'.
w = 8

Simplifying
w = 8

See similar equations:

| x-1/2y=-6 | | -2p+5(-7p-20)=-20p+19 | | X/1.4=28/5.6 | | -44+5y+4=3(3y-5)-5 | | 6/(6x^2) | | 27a^6b^9+c=0 | | 11/7=88/c | | 54-4(6+3*2)+13= | | 5y=2y+2 | | 6/(6x^20 | | -15t+12=-6(4t+7) | | (4x+2)(3x+3)= | | 3.6x=-32.4 | | -16d-2d+16d=18 | | X/5-312 | | 3(2x-1)-4(3x-5)=12 | | W^2-10w+48=0 | | 0.6x+4.4=1.7 | | 20-2(2g+5)=-19g-14+17g | | -9-7x-3y=0 | | 7x-5x=15+2x-3x | | x+100=80 | | 17t+5t-17t-10t=-20 | | 7x+31=4 | | -9-7x-3y=o | | 7+(-3)+(-3)+7= | | -3+7(3q+15)=15q | | 5*x+4=14 | | -6(x+1)-13=10+7 | | 5(x+6)+5x=30 | | X^2-10x=06 | | -5(x+9)-43=7-55 |

Equations solver categories